Factor Analysis of the Brazilian Version of UPPS Impulsive Behavior Scale - Sediyama, Cristina Y. N.; Moura, Ricardo; Garcia, Marina S.; da Silva, Antonio G.; Soraggi, Carolina; Neves, Fernando S.; Albuquerque, Maicon R.; Whiteside, Setephen P.; Malloy-Diniz, Leandro F. (Frontiers in Psychology, 2017)
OBJECTIVE: To examine the internal consistency and factor structure of the Brazilian adaptation of the UPPS Impulsive Behavior Scale. METHODS: UPPS is a self-report scale composed by 40 items assessing four factors of impulsivity: a) urgency, b) lack of premeditation; c) lack of perseverance; d) sensation seeking. In the present study 384 participants (278 women and 106 men), who were recruited from schools, universities, leisure centers and workplaces fulfilled the UPPS scale. An exploratory factor analysis was performed by using Varimax factor rotation and Kaiser Normalization, and we also conducted two confirmatory analyses to test the independency of the UPPS components found in previous analysis. RESULTS: Results showed a decrease in mean UPPS total scores with age and this analysis showed that the youngest participants (below 30 years) scored significantly higher than the other groups over 30 years. No difference in gender was found. Cronbach’s alpha, results indicated satisfactory values for all subscales, with similar high values for the subscales and confirmatory factor analysis indexes also indicated a poor model fit. The results of two Exploratory Factor Analysis were satisfactory. CONCLUSION: Our results showed that the Portuguese version has the same four-factor structure of the original and previous translations of the UPPS. Keywords: Impulsivity, UPPS Impulsive Behavior Scale, Psychometric, UPPS (urgency, lack of premeditation, lack of perseverance, sensation seeking), Executive function.